Efek Ekstrak Etanol Biji Kakao (Theobroma cacao) sebagai Antibakteri terhadap Pseudomonas aeruginosa secara In Vitro (The Effect of Ethanolic Extract of Cocoa Beans (Theobroma cacao) as an Antibacterial against Pseudomonas - Devi Chintya Kumalasari; Enny Suswati; Misnawi Misnawi (Pustaka Kesehatan, 2015)
Nosocomial infection is one of the most serious healthy problem in the world. It causes by Pseudomonas aeruginosa which has a high resistance to antibiotic. One alternative to overcome this problem is the utilization of chocolate (Theobroma cacao) because it contains polifenol that can be used as an antibacterial agent. The aim of this research was to determine antibacterial effect and Minimum Inhibitory Concentration (MIC) of ethanolic extract of cocoa beans to P. aeruginosa by in vitro method. Antibacterial activity test used disk diffusion (Kirby Bauer) method. This type of research was a quasi-experimental with posttest only control group design. Samples used was colony of P. aeruginosa. Concentrations of test solution used were 7,81; 15,62; 31,25; 62,50; 125; 250; 500; and 1000 mg / ml. Positive control used cefepime suspension and negative control used sterile distilled water. The result showed that inhibition zones formed at a concentration of 7,81 mg/ml to 1000 mg/ml. The higher the concentration of the cocoa beans extract, the wider the inhibition zones formed. By direct measurement, MIC was obtained at the dose of 7.81 mg / ml while statistical analysis yielded an MIC value of more than 6.95 mg / ml. In conclusion, the ethanolic extract of cocoa beans had antibacterial effect on P. aeruginosa in vitro.   Keywords: antibacterial effect, cocoa beans, Pseudomonas aeruginosa